Formulation And Evaluation Of Duloxetine Hydrochloride Delayed Release Enteric Coated Capsules - PREETHI MYLAVARAPU; PRATHIMA SRINIVAS; VENKATA RAMANA REDDY; M.SADANANDAM (International Journal of Pharma and Bio Sciences, 2011)
The main objective of the present study is to prepare robust and stable formulation and evaluation of duloxetine hydrochloride delayed release enteric coated pellets in capsules. Since Duloxetine hydrochloride degrades in the acidic environment, it is important to bypass the acidic pH of the stomach. Protection of drug from acidic environment is done by coating the drug with enteric polymers by using suspension layering technique in Fluidized bed processor (FBP) with different enteric polymers like PVAP (Poly vinyl Acetate phthalate), Kollicoat MAE 30 DP, Eudragit L30 D55 (Methacrylic acid copolymer) and HPMCP (Hydroxy propyl methyl cellulose phthalate). Eudragit L30 D55 is a good enteric material. Based on the vendor data and details, drug release shows after pH6.5 buffer, where as marketed preparation release starts at pH 5.5 buffer. So Eudragit was not taken for further trails. The prepared pellets were studied for their Invitro release studies and were analyzed by using HPLC technique. The released kinetics was analyzed using the zero-order model, first-order model and Higuchi’s square root equation. FT-IR (Infrared spectroscopy) and DSC (Differential Scanning Calorimetry) studies were performed to know the compatibility of the drug with various excipients and SEM (Scanning Electron Microscopy) analysis performed to know the particle size and morphology of the pellet. The results depicted that HPMCP gave a good dissolution profile and process suitability compared to Eudragit L30 D55, Kollicoat MAE 30DP and PVAP and hence optimized based on the similarity factor (f2 value).